Analisis Daya Saing Dan Faktor-Faktor Yang Mempengaruhi Ekspor Kayu Lapis Indonesia Ke Jepang Periode 1992-2011 - Adi Putra, I Ketut Bagus Martawan; Aswitari, Luh Putu (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2015)
Indonesia is a country with abundant natural resources. Since the log export ban regulations, the utilization of natural resources is continued to be done by the government in order to increase added value to boost exports in the form of processed wood products, especially plywood, as it motivated the various advantages and Indonesian forestry exports, thus the export competitiveness of the sector are needed to be improved. This study was conducted to determine the development of the competitiveness of Indonesia's plywood exports to Japan in the period of 1992-2011 by using the RCA index (Revealed Comparative Advantage) and multiple linear regression analysis to determine the good effect of it either simultaneously or partially between the US Dollar exchange rate, Total Production and Products Gross Domestic in Japan against Indonesia's plywood exports to Japan by using program analysis of secondary data. The results of data analysis showed the simultaneous US Dollar exchange rate, Total Production and Gross Domestic Product of Japan significantly to Indonesia's plywood exports to Japan in the period of 1992-2011. In partial US Dollar exchange rate, the amount of production, and Japan's gross domestic product and a significant positive impact on Indonesia's plywood exports to Japan period 1992-2011. The calculation of the competitiveness using RCA index indicates the competitiveness of Indonesian plywood exports were high because the index RCA> 1, but Malaysia does not has competitive because the RCA index <1. Indonesia needs to improve and maintain its competitiveness in order to increase the contribution to national revenue.
Keywords: Competitiveness, US Dollar Exchange Rate, Total Production, Japan Gross Domestic Product